Maternal characteristics in obstetric emergency cases at RSUP Dr. M. Djamil Padang - Rena Afri Ningsih; Yusrawati; Aldina Ayunda Insani; Joserizal Serudji (Science Midwifery, 2022)
The causes of maternal death in West Sumatra Province in 2020 are bleeding at 2.1%, hypertension in pregnancy at 1.5%, infection at 0.9%, metabolic disorders at 0.6% and other causes at 3.5%. Cases of maternal death can be caused by obstetric emergencies. This study aims to describe the characteristics of mothers in obstetric emergencies at comprehensive emergency obstetric and newborn care (EmONC) RSUP Dr. M. Djamil Padang. This study is a descriptive study with a population of obstetric emergency cases at EmONC. hospital. Dr. M. Djamil Padang period May-June 2022. The sample is 108 respondents. The results of this study showed that from 108 respondents there were 23.1% of respondents with a diagnosis of severe preeclampsia, 79.6% of respondents aged 20-35 years, 84.3% of respondents with parity ≤ 2, the last education of respondents was senior high school 43.5%, 26.9% of respondents did not work, 81.5% of respondents did not have a history of non-communicable diseases, and 73.1% of respondents had a sufficient number of antenatal care (ANC) visits. Most patients with obstetric emergency cases at EmONC RSUP Dr. Mdjamil Padang with a diagnosis of severe preeclampsia, age 20-35 years, and the number of ANC visits is sufficient.